Perbedaan Gaya Hidup pada Siswa Penerima dan yang Tidak Menerima Kartu Menuju Sejahtera di Yogyakarta - Irnaningsih ,; Indra Wahyudi; FX. Wahyu Widiantoro (LPPM Universitas Proklamasi 45, 2020)
This Study aims to determine the differences in hedonic lifestyle trends between recipient and non recipients towards prosperity in SMA Negeri X Yogyakarta and to find out the tendency of hedonic lifestyle between recipient and non recipient card recipients towards prosperity in SMA negeri X Yogyakarta.This type of research is quantitative research using comparative causal approach. The Subjects of this study were students of class X, XI, and XII with KMS Recipient students and 30 KMS non-Recipients students. The Sampling tehnique used is cluster quota random sampling. Data measurement tool uses hedonic lifestyle scale, validity test uses construct validity, realibility test with a value of 0,912, data analysis uses t-test analysis techniques. The results of the different test (t-test) at the significancelevel of 5% obtained a value of P>0,05, which is 0,957.The results showed a significance value of 0,957, these results meant that there was no difference in the hedonic lifestyle tendencies between recipient and non-recipient students leading to prosperity at SMA Negeri X Yogyakarta.